2014
DOI: 10.1002/app.41631
|View full text |Cite
|
Sign up to set email alerts
|

Metallopolymers based on a polyazomethine ligand containing rigid oxadiazole and flexible tetramethyldisiloxane units

Abstract: Soluble, easily processable polymer-metal complexes with improved optical and dielectric properties for optoelectronic functional materials were obtained. For this, a new polyazomethine (PAZ2) was prepared by the reaction of a siloxane dialdehyde and bis(formyl-p-phenoxymethyl) tetramethyldisiloxane with 2,5-bis(p-aminophenyl)-1,3,4-oxadiazole, and it was used as a ligand for Cu(II), Co(II), and Zn(II) ions on the basis of the presence of the electron-donor nitrogen atoms from the azomethine group and oxadiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…In general, the silicon atom is part of a siloxane moiety, which implies a Si-O bond. [20][21][22][23][24][25] In 2014, Zaltariov et al 26 reported a PAM with a central silicon atom bonded to four carbon atoms complexed with different metal ions. However, they used a methylene unit instead of an aromatic moiety bonded to a silicon atom which, along with other structural features, rendered the polymer too exible; thus, the T g measured for the polymer was 48 C. For a material to be used for charge transport in a PHOLED device, its T g value must be over 100 C to avoid deterioration of its mechanical properties under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the silicon atom is part of a siloxane moiety, which implies a Si-O bond. [20][21][22][23][24][25] In 2014, Zaltariov et al 26 reported a PAM with a central silicon atom bonded to four carbon atoms complexed with different metal ions. However, they used a methylene unit instead of an aromatic moiety bonded to a silicon atom which, along with other structural features, rendered the polymer too exible; thus, the T g measured for the polymer was 48 C. For a material to be used for charge transport in a PHOLED device, its T g value must be over 100 C to avoid deterioration of its mechanical properties under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Siloxane moieties (short segments, long chains, cycles) are often used in LCs as flexible spacers or as the main backbone, in combination with unnumbered mesogenic groups. The main reasons for using siloxanes instead of purely [54,[114][115][116] and illustration through 2D and 3D AFM (a,b) and TEM (c) images of their self-assembly that changes depending on the polarity of the environment.…”
Section: Figurementioning
confidence: 99%
“…Several alternative synthetic strategies such as creation of the molecular asymmetry by incorporating of noncoplanar groups in the main chain, attaching the bulky pendant groups, for instance, the introduction of substituents (alkyl or alkoxy groups) in the ortho-position of the aromatic ring or insertion of aliphatic flexible spacers between aromatic rings within the main chain are approached. 18 Siloxane moiety had also inserted as a flexible spacer, either in the amine or carbonyl component, resulting in polyazomethines with improved solubility [19][20][21][22][23][24][25] because of high flexibility of the siloxane bond and weak intermolecular interactions between dimethylsiloxane units. 4,17 The inclusion of polyazomethines in rotaxane architecture is another strategy approached to improve their processability.…”
Section: Introductionmentioning
confidence: 99%
“…4,17 The inclusion of polyazomethines in rotaxane architecture is another strategy approached to improve their processability. 18 Siloxane moiety had also inserted as a flexible spacer, either in the amine or carbonyl component, resulting in polyazomethines with improved solubility [19][20][21][22][23][24][25] because of high flexibility of the siloxane bond and weak intermolecular interactions between dimethylsiloxane units.…”
Section: Introductionmentioning
confidence: 99%